The Role of Islamic Education Teachers in Instilling the Value of Religious Moderatio Amid the Polemic of Islamophobia - Wirani Atqia; Muhammad Syaiful Riky Abdullah (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2021)
This study aims to find and confirm the role of Islamic Religious Education teachers in instilling the value of religious moderation as an effort to prevent radicalism. With this form of radicalism having a bad effect on citizens and society, this fear has resulted in the emergence of a new perception, namely "Islamophobia". Public fear of Islam, such as acts of radicalism, terrorism, and other things in the name of Islam. so that it is illustrated in the minds of the people that Islam is the culprit for all of these things. This research method uses a qualitative method. Data collection techniques through interviews, observation, and literature study. The results of the study reveal that Islamic religious education teachers in Batang District instill the values ??of religious moderation through learning. Seen in the Learning Development Plan, the teaching materials used, and the learning process. As teachers of Islamic Religious Education, they play an important role in instilling the values ??of religious moderation from an early age starting from the family and school environment.